Short Communication: CPUE, CPUA and distribution patterns of four demersal fishes in coastal waters of the northern Persian Gulf, Iran - FAROKHZAD ZEINALI; EHSAN KAMRANI; MEHRAN PARSA (Nusantara Bioscience, 2017)
Zeinali F, Kamrani E, Parsa M. 2017. Short Communication: CPUE, CPUA and distribution patterns of four demersal fishes in coastal waters of the northern Persian Gulf, Iran. Nusantara Bioscience 9: 12-17. CPUE, CPUA and distribution patterns of Pampus argenteus, Otolithes ruber, Nemipterus japonicas and Saurida tumbil along the coastal waters of Hormozgan province were investigated. The mean CPUE values for P. argenteus in 0-10 m and 10-20 m depth layers was significantly different (P<0.05). The highest and lowest mean CPUE of S. tumbil were observed in 20-30 m and 0-10 m depth layers, respectively. The highest mean CPUA for P. argenteus was found in 0-10 m depth layer, with a descending trend with increasing the depth. The highest CPUA of O. ruber was observed in 10-20 m depth layer, but the mean CPUA values was not significant among depth layers (P>0.05). The mean CPUA for N. japonicas was relatively high in 30-40 m depth layer and markedly lower in 0-10 m depth layer as the shallowest depth layer. The highest and lowest mean CPUA of S. tumbil were observed in 20-30 m depth layer and 0-10 m depth layer, respectively.